Meningkatkan Kemampuan Praktik Siswa Melalui Karya Ecoprint Teknik Pounding Pada Pembelajaran SBDP Di Kelas IV SDN 7 Tapa, Kabupaten Bone Bolango - Nadila Datunsolang; Sukri Katili; Rustam I. Husain; Mimy Astuty Pulukadang; Vicka Muniati Arifin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to improve the practical skills of fourth-grade students at SDN 7 Tapa, Bone Bolango Regency, through ecoprint artwork using the pounding technique in Arts and Culture Education (SBdP) learning. A Classroom Action Research (CAR) design was employed across two cycles, each comprising planning, action implementation, observation, and reflection. The research subjects consisted of 18 fourth-grade students. Data were collected through observation, interviews, performance tests, and documentation, then analyzed descriptively based on four aspects: procedural accuracy, pounding-technique skill, creativity, and product quality. The results showed a gradual improvement, from 17% of students being competent at baseline to 22% in Cycle I Meeting I, 33% in Cycle I Meeting II, 67% in Cycle II Meeting I, and 89% in Cycle II Meeting II. These findings confirm that the ecoprint pounding technique effectively improves elementary students' practical skills in SBDP learning.